1979
DOI: 10.1093/ajcn/32.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Bone status and fracture rates in two regions of Yugoslavia

Abstract: Bone status and fracture rates were evaluated in two Yugoslav populations with very different dietary habits. In district A (Podravina) the daily calcium intake was about twice that in district B (Istra). There were similar but smaller differences in the intakes of other nutrients. In district B metacarpal cortical width was reduced in all age groups of both sexes but the difference tended to decrease with age. The proximal femur fracture rate was higher in district B than district A but there was no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
177
1
12

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(201 citation statements)
references
References 37 publications
9
177
1
12
Order By: Relevance
“…Distal forearm bone mineral content (BMC; g), bone mineral density (BMD; g/cm 2 ), and bone width (cm) were measured by single-photon absorptiometry (SPA) in 120 boys with a mean age of 9.9 years (range 3-17) and 94 girls with a mean age of 10.7 years (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The children were included from three published cohort studies between the years 1979-1981: 48 boys and 28 girls with a previous fracture 16 , 31 boys and 25 girls with premature birth 17 and 41 boys and 43 girls from a healthy control cohort within same ages [16][17][18] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distal forearm bone mineral content (BMC; g), bone mineral density (BMD; g/cm 2 ), and bone width (cm) were measured by single-photon absorptiometry (SPA) in 120 boys with a mean age of 9.9 years (range 3-17) and 94 girls with a mean age of 10.7 years (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The children were included from three published cohort studies between the years 1979-1981: 48 boys and 28 girls with a previous fracture 16 , 31 boys and 25 girls with premature birth 17 and 41 boys and 43 girls from a healthy control cohort within same ages [16][17][18] .…”
Section: Methodsmentioning
confidence: 99%
“…There are no prospective studies that have followed bone mass from young adulthood into the ages when osteoporosis becomes a problem of magnitude. However calculations have inferred that 50% of the variance in BMD at age 65 could be predicted by peak bone mass [3][4] it has also been shown that individuals with high bone mass at age 30 are likely to have high bone mass also at age 70 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, quanto maior a necessidade e menor o fornecimento dietético, mais eficiente será a absorção. O aumento das necessidades do elemento encontrado em situações como crescimento, gravidez, (12). Como o leite e outros produtos lácteos são as fontes principais do elemento, as crianças que não os consomem, ou os ingerem em quantidades limitadas, estão em risco de deficiência de Ca (13).…”
Section: Absorção De Cálcio Durante a Vidaunclassified
“…Moreover, an analysis of studies evaluating the effect of exercise on bone density (Specker, 1996) showed that, at least for spine bone mineral density, a calcium intake of more than 1000 mgaday is necessary before exercise can exert a positive effect on bones. Finally, both crosssectional (Matkovic et al, 1979) and perspective (Holbrook et al, 1988) studies showed a higher risk of hip fractures in subjects with lower calcium intakes, while guidelines for osteoporosis treatment and prevention suggests dietary calcium supplementations (Castelo-Branco, 1998). Various studies (Scaccini et al, 1992;Howarth et al, 1995) have tried to understand what factors in¯uence calcium intake.…”
Section: Reducing Lipid Level Improves Calcium Intake a Gaddi Et Almentioning
confidence: 99%